Lepidoptera phylogeny and systematics: the state of inventorying moth and butterfly diversity - Kristensen, Niels P.; Scoble, Malcolm J.; Karsholt, Ole (Zootaxa, 2007)
The currently recognized robust support for the monophyly of the Lepidoptera (and the superorder Amphiesmenoptera comprising Lepidoptera + Trichoptera) is outlined, and the phylogeny of the principal lineages within the order is reviewed succinctly. The state of the taxonomic inventory of Lepidoptera is discussed separately for ‘micro-moths’, ‘macro-moths’ and butterflies, three assemblages on which work has followed historically somewhat different paths. While currently there are about 160,000 described species of Lepidoptera, the total number of extant species is estimated to be around half a million. On average, just over one thousand new species of Lepidoptera have been described annually in recent years. Allowing for the new synonyms simultaneously established, the net increase in species numbers still exceeds 800/year. Most of the additions are foreseeable in the micro-moth grade, but even for butterflies ca 100 species are added annually. Examples of particularly interesting new high-rank taxa that have been described (or whose significance has become realized) since the middle of the 20th century include the non-glossatan lineages represented by Agathiphaga and Heterobathmia and the heteroneuran families Andesianidae, Palaephatidae, Hedylidae and Micronoctuidae. Some thoughts on how present and future systematic lepidopterology might be prioritised are presented.